2020
DOI: 10.36713/epra4834
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Marketing on Instagram: When Is the Most Effective Posting Timing?

Abstract: This study investigates the most effective posting timing on Instagram to enhance content engagements (i.e., likes and comments). Data of 2,958 Indonesian food brands posts were analysed using negative binomial regression to predict the number of likes and comments. This study reveals that the most effective posting days are on Monday, Tuesday, Wednesday, Thursday, and Friday as contents posted on Instagram on these days result in a higher number of likes and comments. In addition, this study also encourages f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition to the existing literature by Jahanbakhsh et al (2021) on the timing of social media posts, this study primarily focused on gaining insights into user activity information to gain business insights from the analytical data. This study adds to the existing research of Hanifawati et al (2019) and Wahid and Wadud (2020) to determine when is the most effective timing of user engagement on social media business pages by focusing on Great Deal Tires analytics data. With respect to the Facebook analytics data, the study agreed to the outcome of Pollard (2015) that identified highest user engagement in between 9 a.m. and 7 p.m. but also extended it by providing accurate date and time for the selected company.…”
Section: Implications Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the existing literature by Jahanbakhsh et al (2021) on the timing of social media posts, this study primarily focused on gaining insights into user activity information to gain business insights from the analytical data. This study adds to the existing research of Hanifawati et al (2019) and Wahid and Wadud (2020) to determine when is the most effective timing of user engagement on social media business pages by focusing on Great Deal Tires analytics data. With respect to the Facebook analytics data, the study agreed to the outcome of Pollard (2015) that identified highest user engagement in between 9 a.m. and 7 p.m. but also extended it by providing accurate date and time for the selected company.…”
Section: Implications Of the Studymentioning
confidence: 99%
“…This study adds to the existing research of Hanifawati et al. (2019) and Wahid and Wadud (2020) to determine when is the most effective timing of user engagement on social media business pages by focusing on Great Deal Tires analytics data. With respect to the Facebook analytics data, the study agreed to the outcome of Pollard (2015) that identified highest user engagement in between 9 a.m. and 7 p.m. but also extended it by providing accurate date and time for the selected company.…”
Section: Implications Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the probability of brands' posts to be seen by and engaged with Instagram users. Meanwhile, during weekends and dinner time become not ideal time because users have many activities such as interact with family member or playing video game, instead of scroll Instagram content(Wahid and Wadud, 2020). Another research in Indonesia context shows the trend of time post by the open trip Instagram account.…”
mentioning
confidence: 99%
“…Brands that already have a structured and consistent activity posting pattern have the possibility of using Instagram Scheduling Tools. They expect their promotional content to reach the optimal audience and become one of the guidelines for improving brand and product marketing strategies through the Instagram platform(Wahid and Wadud 2020). On the table 2 below shows summary of total posting activity for each brand, we can see that based on the day, 3 of the five skincare local brands post the most on Fridays while, based on the total time, it is 06.00 pm and 10.00 am.…”
mentioning
confidence: 98%